Reverse Social Impact of Oil Palm Plantation Expansion: A Study of Three Communities in Jambi, Indonesia - Pahmi, Pahmi; Gunawan, Budhi; Iskandar, Johan; Soemarwoto, Rini (Forest and Society, 2023)
Studies on the social impacts of oil palm development have focused on various communities with distinct characteristics. Due to the rarity of comparative investigations, this study aimed to examine the impact of oil palm plantation expansion on the Suku Anak Dalam, Jambi Malay, and the Javanese transmigrant, the three communities with different socio-economic characteristics. In-depth interviews and observations were conducted to understand the communities' interaction and dependence on forest resources. The study also conducted a household census to assess 67 Malay and 66 Javanese transmigrant families. However, a household census could not be conducted to asses 45 families of the Suku Anak Dalam due to some limitations. This necessitated indirect data collection through the community leader. The results showed that the oil palm development significantly and negatively impacts the Suku Anak Dalam more than the Malay community and the Javanese transmigrant. The Suku Anak Dalam face difficulties in meeting their basic needs because the conversion of forest areas into oil palm plantations has reduced their access to these resources. In contrast, the Malay community and the Javanese transmigrants have enjoyed various benefits, such as ownership of oil palm gardens, employment opportunities as daily laborers, and partnerships with companies through the nucleus-plasma program. Therefore, it is crucial for the government to protect the Suku Anak Dalam community from the negative impacts of oil palm plantation development activities.